PENGUATAN EKONOMI KELUARGA MELALUI PENINGKATAN LITERASI BAHAYA PINJAMAN ONLINE ILEGAL DAN JUDI ONLINE DI DESA TAMBANG AYAM - Kutria Lasmawati, Siti Dewi (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
Strengthening family finances is a crucial step in improving community well-being, particularly in villages vulnerable to financial challenges. This Community Service activity aims to increase community literacy in Tambang Ayam Village, Anyer District, regarding the dangers of illegal online loans (pinjol) and online gambling, which are rampant and can negatively impact family finances. This activity was implemented through outreach, interactive discussions, and simple financial management simulations to help the community recognize risks and avoid harmful financial practices. The results of the activity indicate an increase in understanding among Tambang Ayam Village residents regarding the definition, legal basis, and characteristics of illegal online loans, the economic and social impacts of online gambling, and the importance of wise family financial management. This Community Service activity is expected to strengthen family economic resilience while reducing the potential for social problems resulting from entanglement in online loans and online gambling.